Оплакувальні мотиви в текстах Святого Письма - Микитюк, Галина; Mykytiuk, Halyna (Східноєвропейський національний університет імені Лесі Українки, 2015)
У статті досліджено текст Старого та Нового Завітів на наявність у них оплакувальних мотивів, що є характерною рисою барокового жанру плачу (ляменту). Проаналізовано особливості оплакувальної поетики, що відіграє значну роль у розкритті та сприйманні реципієнтом ідеї Бога та божественного.The special emotional load in the text of the Bible is in the episodes that are associated with loss, death and accompanied by a complaint and a lamentation. The crying as an independent genre of Baroque is not established of the canonical Christian tradition. But there are places in the Old and the New Testament, where the tragic events and feelings are transferred to the poetics of crying. The article investigates how the archaic ceremonial of the mourning influenced the formation of sensory-imagery system of Scripture. Analyzed verbal formula display motives of crying: expression of grief and despair, symbolism for the traditional funeral rite, rhetorical figures.
Motives of Crying in the Texts of Holy Scripture
Keywords: експресія; мотив плачу; оплакувальна поетика; Святе Письмо; Біблія; expression; motive of crying; mourning the poetics; Holy Scripture; Bible